(untitled) (Marketing Journal, 2025)
This article analyzes the importance of brand value in entrepreneurial activity and the methods of its evaluation. Market -based, income -based, cost -based approaches, as well as the Net Promoter Score (NPS) method, were applied to assess brand value. Using the example of the “Ideal” brand from Namangan, practical calculations were carried out, and comparative results were presented. The findings indicate that the income -based approach provides a more accurate assessment of brand value and reflects its long -term development potential.